2022
DOI: 10.1029/2021jd036296
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Determination of the Relationship Between Organic Aerosol Viscosity and Ice Nucleation at Upper Free Tropospheric Conditions

Abstract: Cirrus clouds play an important role in Earth's energy budget by reflecting the incoming solar radiation into space which leads to cooling, and by reducing the infrared longwave coming from the Earth surface which leads to warming (Chen et al., 2000;Heymsfield et al., 2017;Storelvmo & Herger, 2014). The radiative properties of cirrus clouds depend on the ice crystal number concentration, which in turn depends on the aerosol that nucleate ice at these conditions. Cirrus cloud ice crystals form either through ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 126 publications
(295 reference statements)
0
12
0
Order By: Relevance
“…For example, the long-range transport of pollutants depends on SOA viscosity. In addition, predictions of gas-particle partitioning (and hence, aerosol mass and size distributions) depend on the viscosity of SOA. Similarly, heterogeneous chemical reactions , and photochemical reactions , in SOA depend on the mobility and uptake of reactants and products, which can be inhibited at high viscosity. Furthermore, some studies suggest that SOA particles in a glassy phase state (η > 10 12 Pa s) might be good heterogeneous ice nuclei and thus affect the microphysical and radiative properties of clouds. However, this is an area of active debate, and a recent study reported that heterogeneous ice formation on glassy SOA may be uncommon for tropospheric conditions …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the long-range transport of pollutants depends on SOA viscosity. In addition, predictions of gas-particle partitioning (and hence, aerosol mass and size distributions) depend on the viscosity of SOA. Similarly, heterogeneous chemical reactions , and photochemical reactions , in SOA depend on the mobility and uptake of reactants and products, which can be inhibited at high viscosity. Furthermore, some studies suggest that SOA particles in a glassy phase state (η > 10 12 Pa s) might be good heterogeneous ice nuclei and thus affect the microphysical and radiative properties of clouds. However, this is an area of active debate, and a recent study reported that heterogeneous ice formation on glassy SOA may be uncommon for tropospheric conditions …”
Section: Introductionmentioning
confidence: 99%
“…52−58 However, this is an area of active debate, and a recent study reported that heterogeneous ice formation on glassy SOA may be uncommon for tropospheric conditions. 59 In addition to the gaseous components that can lead to SOA formation, biomass burning also directly emits organic aerosols into the atmosphere, referred to as biomass burning primary organic aerosol (BB-POA). The viscosity of BB-POA from the pyrolysis of pine wood has been studied previously and was found to depend strongly on relative humidity (RH) and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…However, we note that dicarboxylic acids and secondary organic aerosol generated from oxidation ow reactors have shown evaporation just a few degrees warmer than the transition temperature. 15,20,27 A related question is whether particles achieve equilibrium with respect to viscosity during transit in the thermal conditioner. Modelling studies with the KM-GAP model suggest that equilibration timescales for sucrose and citric acid are <11 s for the 10 6 Pa s phase transition, if the phase transition occurs at T > ∼ −25 °C.…”
Section: Discussionmentioning
confidence: 99%
“…7 This viscosity typically occurs at temperatures ∼20-30 K warmer than the glass transition temperature for complex organic mixtures. 20 For reference the diffusion coefficient implies an intraparticle mixing time of ∼9.6 hours for 300 nm particles and ∼5.8 min for 30 nm particles. Zhang et al, 16 Järvinen et al, 14 and Bell et al 17 measured the sintering of agglomerates formed by natural coagulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation